ICT innovations 2017 : data-driven innovation : 9th International Conference, ICT Innovations 2017, Skopje, Macedonia, September 18-23, 2017, Proceedings /: data-driven innovation : 9th International Conference, ICT Innovations 2017, Skopje, Macedonia, September 18-23, 2017, Proceedings. (2017) - Unknown
No abstract available